Water walking as a new mode of free surface skipping - Hurd, Randy C. (Sci Rep, 2019)
Deformable elastomeric spheres are evaluated experimentally as they skip multiple times over a lake surface. Some spheres are embedded with small inertial measurement units to measure the acceleration experienced during water surface impact. A model for multiple impact events shows good agreement between measured acceleration, number of skipping events and distanced traveled. The experiment reveals a new mode of skipping, “water walking”, which is observed for relatively soft spheres impacting at low impact angles. The mode occurs when the sphere gains significant angular velocity over the first several impacts, causing the sphere to maintain a deformed, oblong shape. The behavior is characterized by the sphere moving nearly parallel to the water surface with the major axis tips dipping below the water surface with each rotation while the shorter sides pass just above, giving the impression that the sphere is walking across the water surface.